253 Physiological Responses to Heat Stress of Holstein Heifers Carrying the SLICK1 Allele of the Prolactin Receptor (PRLR) Gene. (8th October 2021) - Denicol, Anna C; Carmickle, Allie T; Pereira, Jessica; Ferreira, Fernanda C; Larson, Colleen C; Sosa, Froylan; Jansen, Laura; Haimon, McKenzie L; Hansen, Peter J
Abstract: The objectives of this study were to evaluate physiological responses to heat stress of Holstein heifers carrying the SLICK1 allele of the PRLR, i.e., the slick mutation. Slick and non-slick females were produced in central CA (n = 3 farms) and south FL (n = 3 farms) by inseminating cows with semen from two heterozygous slick Holstein sires. In July 2020, a subgroup of heifers of both genotypes (slick=93; non-slick=110) and two age groups (Group 1: 6–8 months old; n = 131; Group 2: 9–51 days old; n = 72) in both states were evaluated for rectal temperature (RT), surface temperature (ST) and sweating rate (SR). Dry bulb temperature, relative humidity and dew point were recorded every 15 min during testing for temperature humidity index (THI) calculation. Statistical models included the effects of genotype, state, farm within state, group, sire, THI, and interactions. Significant effects were considered as those with P < 0.05. Although the THI in CA was lower than FL (80 ± 0.1 vs 84 ± 0.2; P < 0.01), both were above 77 (estimated heat stress threshold for young animals). Slick heifers raised in FL had lower RT compared to non-slick siblings (39.6 ± 0.1 vs 40.1 ±0.1; genotype P < 0.01); this difference was not observed in CA (39.1 ± 0.04 vs 39.1 ± 0.05; genotype P = 0.5; state x genotype P < 0.01). In both states, slick heifers tended to have lower ST (34.7 ± 0.2 vs 35.1 ± 0.2; P = 0.07); CA heifers had lower RT and ST and higher SR (P < 0.01) regardless of genotype. Current results show that presence of the SLICK1 allele can improve the ability of Holstein heifers to regulate body temperature, particularly in high humidity conditions. Next steps will include analysis of performance as study animals enter the reproductive phase. Funding sources: Holstein Association USA and L.E. "Red" Larson Endowment.